P268 Eosinophil-derived neurotoxin (eosinophil protein x) showed higher specificity and positive predictive value for detecting disease activity in inflammatory bowel disease compare to faecal calprotectin. (25th January 2019) - Lyutakov, I; Nakov, R; Nakov, V; Vladimirov, B; Asenova, B; Chetirska, M; Dimov, A; Vatcheva-Dobrevska, R; Penchev, P
Abstract: Background: Colonoscopy with multiple biopsies represents the gold standard to diagnose patients with chronic diarrhoea and to assess disease activity and severity. However, it is invasive and costly. Faecal calprotectin (FC) is used as a biomarker for intestinal inflammation in inflammatory bowel disease (IBD) but there is no reliable marker for microscopic colitis (MC). Moreover, the best biomarker for distinguishing functional from organic intestinal disorders is elucidated. Methods: The AIM is to evaluate the diagnostic accuracy of faecal eosinophil-derived neurotoxin/eosinophil protein x (EDN/EPX) and to compare it to FC in patients with chronic diarrhoea. In this prospective study, we enrolled 40 adult patients with chronic diarrhoea who underwent standard laboratory test, colonoscopy, faecal EDN/EPX and FC at 'Tsaritsa Yoanna – ISUL' University Hospital, Sofia, Bulgaria. We divided the patients into five groups: 14 patients with active IBD, 5 patients with quiescent IBD, 5 patients with IBD after surgery, 11 patients with IBS-D, and 5 patients with MC. We used ELISA to detect EDN/EPX and quantitative immunochromatographic to evaluate FC. Results: Of this 40 patients included in the analysis, elevated levels of EDN/EPX was confirmed in 25% (10) of the patients and excluded in 75% (30). We found a EDN/EPX cut-off level of 1357 ng/ml for IBD activity with sensitivity of 50.00% (95% CI 23.04% to 76.96%), specificity 88.46% (95% CI 69.85% to 97.55%), negative predictive value 76.67% (95% CI 65.65% to 84.96%) and positive predictive value (PPV) of 70.00% (41.61% to 88.43%). EDN/EPX showed higher specificity and PPV for detecting disease activity in IBD patients compared with FC. Conclusions: Combination of EDN/EPX and FC should be used for identifying patients with active IBD and they could possibly be used as biomarkers for differentiating IBD from IBS-D or MC with high diagnostic accuracy. Combination of both EDN/EPX and FCP can be used as a screening and monitoring surrogate markers for non-invasive disease activity evaluation in patients with active IBD using both their NPV and PPV. Furthermore, bigger studies are needed to establish the efficacy of EDN/EPX.